INCREASING THE STUDENTS’ READING COMPREHENSION BY USING RECIPROCAL TEACHING STRATEGY - Arif, Abdul (IKIP PGRI Pontianak, 2014)
This research was aimed at finding out: (1) whether or not Reciprocal Teaching Strategy significantly increased the students’ achievement in reading comprehension; (2) the effect size of the strategy in increasing the students’ achievement. This research was a pre- experimental study using one group pretest-posttest design carried out at the eleventh grade students of SMA Muhammadiyah 1 Pontianak in the Academic Year of 2011/2012. The data were collected by using measurement technique. Data analysis showed that t-value was higher than t-table (2.127>2.021) at 0.05 level of significance. It means that the alternative hypothesis is accepted and the null hypothesis is rejected. The mean score of pre-test was 51.5 and the mean score of post-test was 80.8. Thus, it can be concluded that the use of Reciprocal Teaching Strategy significantly increases the students’ reading comprehension. The analysis of effect size showed that the effect size was categorized as high category. Thus, it can be concluded that the use of reciprocal teaching strategy highly influenced the students’ reading comprehension and was considered as effective teaching strategy in increasing the students’ reading comprehension. Keyword: Increasing, Reciprocal, Reading Comprehension